Efeitos do represamento sobre o estado nutricional de cinco espécies do gênero Astyanax do rio Iguaçu - Pereira, Larissa Strictar (2012)
The colonization of new reservoirs tends to support those opportunistic species. It is frequently that in this process the species present a change in diet due to the resources availability. Many fish species are widely recognized to change their feeding habits immediately after reservoir construction. However, it remains unknown whether the effects of these changes in feeding and food consumption have positive effects on the nutritional state of the fish, with the possibility of increasing individual fitness. The aim of the present study was to evaluate changes in the feeding activity and nutritional status for five sympatric species from the genus Astyanax in the Salto Caxias reservoir, considering areas impacted at various levels by damming. Sampling was carried out during the pre- and post-filling phases of the Salto Caxias reservoir in four locations in the main body of the Iguaçu river (upstream, transition zone, dam and downstream). The feeding activity and the nutritional status were inferred by the mean stomach repletion index and the mean condition factor, respectively. A general tendency for the feeding activity in the post-damming period to decrease was observed for four of the five considered species. In general, the condition factor decreased for all species in the dam and downstream region. These observations suggest that regardless of whether the diet is altered, the reflections in the nutritional status are negative in altered environments. The nutritional deficit occurs if the diet is altered due to the adaptive limitations in the use of the resources and if the diet remains unaltered due to the scarcity of the preferential food.